Comparison of analgesic efficacy of wound infiltration with bupivacaine versus mixture of bupivacaine and tramadol for postoperative pain relief in caesarean section under spinal anaesthesia: A double-blind randomized trial - Roopa Sachidananda; Vikas Joshi; Safiya I Shaikh; G Umesh; T Mrudula; M Marutheesh (Wolters Kluwer Medknow Publications, 2017)
Background: Caesarean section is one of the most frequently performed surgeries in obstetrics. Optimal pain relief of the mother is possible with multimodal methods. Wound infiltration is one of the simplest and safe methods. The aim of the study was to compare the analgesic efficacy of wound infiltration of bupivacaine, with tramadol and bupivacaine mixture for postoperative pain. Materials and Methods: After obtaining Institutional Ethical Committee approval, 60 pregnant women of age group 18-35 years, undergoing elective caesarean section under spinal anaesthesia were included in the study. The patients were randomized into two groups of 30 each. Patients belonging to group B received bupivacaine 0.25% 0.7 mg/kg (diluted to 20 mL with normal saline), while those belonging to group T received tramadol 2 mg/kg mixed in bupivacaine 0.25% 0.7 mg/kg (diluted to 20 mL with normal saline). The time for first request of analgesia, numerical rating scale score, and cumulative consumption of diclofenac and tramadol in 24 h were compared. Results: The time for first request of analgesia in group T was 386.17 ± 233.84 min compared to group B which was 192.50 ± 134.77 (P < 0.0002). The total diclofenac consumption in the first 24 h was significantly reduced in group T when compared to group B (P < 0.0068). Conclusions: Subcutaneous wound infiltration with tramadol and bupivacaine prolongs the pain-free period and analgesic consumption after caesarean section, while it also enhances the patient satisfaction.